Magic Tree House, Merlin Missions: Balto of the Blue Dawn - Book 26 - Osborne, Mary Pope; Murdocca, Sal (New York : Random House, 2016)
"Jack and Annie travel back in time to 1925 Nome, Alaska, where they meet Balto, the famous sled dog, and help save the town from illness"--
Keywords: Time travel -- Juvenile fiction; Magic -- Juvenile fiction; Sled dog racing -- Juvenile fiction; Balto (Dog) -- Juvenile fiction; Dogs -- Juvenile fiction; Time travel -- Fiction; Magic -- Fiction; Sled dog racing -- Fiction; Balto (Dog) -- Fiction; Dogs -- Fiction; JUVENILE FICTION / Action & Adventure / General; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Historical / General; Alaska -- Juvenile fiction -- History -- 20th century; Alaska -- Fiction -- History -- 20th century; Time travel fiction